Integrated KT 2.0: The next generation of teamwork: IJPDS (2017) Issue 1, Vol 1:187, Proceedings of the IPDLN Conference (August 2016) - Fransoo, Randy; Sibley, Kathryn (International Journal of Population Data Science, 2017)
ABSTRACT Objective The goal of this study was to engage members of a long-standing Integrated KT collaborative in a process to revitalize team goals and processes. “The Need to Know” Team started in 2001 in Manitoba, to engage knowledge users in the conceptualization, creation, and application of population health research. The team has garnered numerous national awards and citations for its approach. We conducted a survey of team members (N=27), representing all Health Authorities in the province, plus provincial government reps. Questions included frequency of data use and medium (print vs online), how well the team is meeting is goals, open-ended questions about how the team could be more useful to members and their organizations, and their top 3 suggestions to ensure the ongoing success and increase the impact of the team. Method Twenty-two of 27 members responded to the survey (81.5%) within one week. Responses to questions about how well the team is meeting its existing goals revealed high scores – especially among those goals which lay entirely within the scope of the team’s control (91% extremely or moderately well). Objectives relating to larger-scale impacts on the healthcare system had lower ratings (72% extremely or moderately well), as might have been expected. Results Over 75% reported that the team’s work had impacted their organization’s work moderately or a lot. The most commonly cited examples were that the work of the team increased capacity for data analysis/interpretation and research (18%), provided results that were used in staff and/or board meetings (15%), influenced decisions and the discussions leading up to them (15%), influenced the development and use of region-relevant quality indicators (13%), and were used in the ongoing education of health professionals (13%). The open-ended questions regarding optimal next steps solicited a variety of suggestions ranging from developing even richer relationships with existing partners, to including a wider variety of partner organizations (e.g. Indigenous groups); aligning team priorities with those of the provincial government (where feasible); and moving to occasional electronic meetings for appropriate content issues and to increase impact in partner organizations. Conclusion This exercise in reflection and strategic planning has shown that the team has done an exceptional job in achieving its initial goals, most of which remain relevant, but some of which need revision. More importantly, several creative approaches have been suggested which may increase future impact and enhance both the breadth and depth of the team’s reach.